Review on Natural Emulsifiers from Niger Seed Oil (Guizotia abyssinica): A Sustainable Alternative for Food Applications - , Omkar S. Kale., Deepak. T. Bornare, Swapnil. S. Jaiswal (Archives of Current Research International, 2025)
Background: Niger seed oil (Guizotia abyssinica) has emerged as a promising plant-based emulsifier due to its unique composition high linoleic acid, phospholipids, and natural antioxidants (tocopherols, polyphenols). Aims: This review evaluates the emulsification properties, oxidative stability, and functional performance of Niger seed oil (Guizotia abyssinica) as a natural alternative to synthetic emulsifiers in food applications, and to compare its efficacy with conventional plant-based and synthetic emulsifiers. Method: This review evaluates its emulsification potential, comparing its performance with synthetic and conventional plant-based emulsifiers (e.g., soy lecithin, polysorbate 80). Niger seed oil demonstrates excellent interfacial activity, oxidative stability, and hypoallergenic properties, addressing health concerns linked to synthetic emulsifiers (e.g., gut microbiota disruption) and allergenic risks of soy/egg-derived alternatives. Challenges like lower phospholipid yield and supply chain limitations are discussed, along with solutions such as enzymatic modification. Empirical Review: The Review highlights Niger seed oil’s potential to meet clean-label demands in bakery, dairy, and pharmaceutical applications, advocating for further research to optimize extraction and commercialization. Recent advances in monoglyceride production have focused on enzymatic glycerolysis as an alternative to conventional chemical synthesis. Lipase-catalyzed reactions offer advantages including milder processing conditions (40-70°C), higher specificity for monoglyceride formation, and avoidance of undesirable side products like soaps. Immobilized lipases from Rhizomuc or miehei or Candida Antarctica have shown particular efficacy in converting oils to monoglycerides with yields exceeding 70% under optimized conditions. Conclusion: Niger seed oil exhibits superior potential as a clean-label emulsifier, combining effective functionality with health benefits. While enzymatic modification significantly improves performance, further optimization is needed for commercial adoption. This natural alternative could reduce reliance on synthetic additives in food processing while maintaining product quality.